2020
DOI: 10.5798/dicletip.755706
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Malondialdehyde and Antioxidant Enzyme Levels with Peritonitis Severity in Patients with Generalized Peritonitis

Abstract: Objective: Generalized peritonitis is fairly common with very high mortality of delayed diagnosis and treatment of infectious condition. In this study, we aimed to determine the effectiveness of malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and C-reactive protein (CRP) levels in peritonitis severity.Methods: This study was planned prospective and randomized. Study consisted of three groups. Each group had 50 patients. Group 1, patients with generalize peritonitis ; Group 2,patients with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The C‐reactive protein is an acute phase reactant. Its value increases in correlation with the severity of inflammation 30 . Studies have found that CRP has a high sensitivity in the diagnosis of AA 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C‐reactive protein is an acute phase reactant. Its value increases in correlation with the severity of inflammation 30 . Studies have found that CRP has a high sensitivity in the diagnosis of AA 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Its value increases in correlation with the severity of inflammation. 30 Studies have found that CRP has a high sensitivity in the diagnosis of AA. 31 These findings are compatible with our study.…”
Section: Ta B L E 2 Laboratory Parameters Of Groups F I G U R Ementioning
confidence: 99%
“…The C-reactive protein is an acute phase reactant. Its value increases in correlation with the severity of inflammation (31). Studies have found that CRP has a high sensitivity in the diagnosis of AA (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that lipids are one of the main targets of oxidation damage to reactive oxygen species, because there occurs dysbalance between formation and neutralizations of free-radical compounds (Nesterov et al, 2018). Intensification of free-radical oxidation of lipids leads to progression of the pathological processes, accompanied by lesions of the liver, first of all, as a result of damage to hepatocytes, their edema, ruination of mitochondria and lysosomes, influx of highly toxic products of cellular metabolism into blood and lysosome enzymes (Savchenko et al, 2017;Dalbaşı et al, 2020;Verveha, 2021).…”
Section: Introductionmentioning
confidence: 99%